Exploring The Potential Of Artificial Intelligenge And Personalized Services In Transforming The Golf Industry - Supari, Supari; Salat, Roy; Wibawa, Tio Anta; Dewi, Nurma Gupita (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The golf industry, steeped in tradition and characterized by its unique culture, is currently at a crossroads, facing both unprecedented opportunities and significant challenges as it navigates the integration of Artificial Intelligence (AI) and personalized services. As technology advances, AI is becoming increasingly pivotal in transforming various aspects of golf, from enhancing equipment and training methodologies to optimizing golf course management through data-driven insights and automation. This integration not only improves operational efficiency but also enriches the overall golfing experience for players by tailoring services to meet their individual needs. Meanwhile, personalized services, which range from customized coaching programs to bespoke membership experiences, are gaining traction as a means to boost customer satisfaction and loyalty within the industry. However, the potential of these innovations is tempered by various barriers, including resistance to technological change, privacy concerns, and the need for significant investment in infrastructure. This paper aims to explore the multifaceted role of AI and personalized services in the golf industry, highlighting the opportunities they present for revenue generation and market expansion, while also addressing the challenges that must be overcome to fully realize their benefits. By examining the current landscape, this research provides insights into how the golf industry can adapt and thrive in a rapidly evolving technological environment, ensuring its relevance and sustainability amid changing consumer expectations and competitive pressures.